A performatividade da recepção na arte contemporânea: o outro experimentador nos processos de criação de Lygia Clark, Ricardo Basbaum e Cláudio Bueno - Panão, Josy Anne Neves (2014)
In contemporary art, we come across an increasing number of processual works which, given their condition of incompleteness, demand a more active and performative reception. Thus, the aim of this research is to analyze creation processes that require reception for the work to happen. The direct action or presence of reception, of this other experimenter who completes the act of creation, is a key element for the artistic proposition to acquire meaning and have the power to disrupt the traditional contemplative patterns of aesthetic fruition and resonate through the sensorial-bodily experience. Therefore, within a very specific crosssection, we exclusively analyze Lygia Clark s proposals Caminhando [Walking] and Estruturação do Self [Structuring of the Self] (featuring her Relational Objects), created between the 1960s and 1980s and, up until more recently, the Superpronome [Superpronoun] proposals by Ricardo Basbaum; and Casa Aberta [Open House] and Redes Vestíveis [Wearable Networks], both by Cláudio Bueno. We observe a great deal of attention given to the presence and action of reception in the poetics of these artists, who opened up their practices and actions to performativity, experience and the making of the other. In the meeting of art and communication, and setting our theoretical and methodological framework on the theory of creation processes conceived by Cecilia Almeida Salles, who based her ideas on references to the critique of process to combine the Peircean semiotics and Pierre Musso's concept of network, we look into these artistic proposals through the concept of communicative act, developed by Salles, in order to delve into the subjectivity nuances of this other experimenter that appears in the creation processes of these artists. Therefore, we look into reception through artistic and creative procedures that trigger processes of singularization, collectivization and action in networks